Functional outcome and patient satisfaction with a ‘self-care’ protocol for minimally displaced distal radius fractures - Owen Bodger (Bone and Joint Open, 2022)
AimsWe introduced a self-care pathway for minimally displaced distal radius fractures, which involved the patient being discharged from a Virtual Fracture Clinic (VFC) without a physical review and being provided with written instructions on how to remove their own cast or splint at home, plus advice on exercises and return to function.MethodsAll patients managed via this protocol between March and October 2020 were contacted by a medical secretary at a minimum of six months post-injury. The patients were asked to complete the Patient-Rated Wrist Evaluation (PRWE), a satisfaction questionnaire, advise if they had required surgery and/or contacted any health professional, and were also asked for any recommendations on how to improve the service. A review with a hand surgeon was organized if required, and a cost analysis was also conducted.ResultsOverall 71/101 patients completed the telephone consultation; no patients required surgery, and the mean and median PRWE scores were 23.9/100 (SD 24.9) and 17.0/100 (interquartile range (IQR) 0 to 40), respectively. Mean patient satisfaction with treatment was 34.3/40 (SD 9.2), and 65 patients (92%) were satisfied or highly satisfied. In total there were 16 contact calls, 12 requests for a consultant review, no formal complaints, and 15 minor adjustment suggestions to improve patient experience. A relationship was found between intra-articular injuries and lower patient satisfaction scores (p = 0.025), however no relationship was found between PRWE scores and the nature of the fracture. Also, no relationship was found between the type of immobilization and the functional outcome or patient satisfaction. Cost analysis of the self-care pathway V traditional pathway showed a cost savings of over £13,500 per year with the new self-care model compared to the traditional model.ConclusionOur study supports a VFC self-care pathway for patients with minimally displaced distal radius fractures. The pathway provides a good level of patient satisfaction and function. To improve the service, we will make minor amendments to our patient information sheet.